The Antioxidant System of the Respiratory Tract. The Intracellular Antioxidant Protection in the Respiratory Tract (Part 3) - A.E. Abaturov; A.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2016)
The literature review presents the current data on glutathione and glutathione-dependent enzymes that play a central role in the functioning of the intracellular antioxidant protection in the respiratory tract. The place of glutathione in oxidation reactions, detoxication and regulation of the activity of intracellular signal transduction pathways are considered in detail. The physiological role and effects of glutathione action are presented.